The Effectiveness of Arbitration as an Alternative to Business Dispute Resolution: Between Procedural Efficiency and Certainty of Adjudication - Refli Attalariq Pane; Raihan Ryanta Akbar; Ahmad Syahbuddin Ritonga; Ibnu Zarir; Zulfarhan Ibrahim Harahap (ISNU Sumatera Utara, 2024)
The development of increasingly complex business activities demands a dispute resolution mechanism that is not only able to provide legal certainty, but also ensure the efficiency of the case settlement process. Arbitration is present as an alternative dispute resolution that offers procedural flexibility, confidentiality, and faster resolution than litigation. However, the effectiveness of arbitration is not only determined by procedural efficiency, but also by the certainty of the implementation of the award. This study aims to analyze the effectiveness of arbitration as an alternative to business dispute resolution by focusing on the relationship between procedural efficiency and the certainty of award implementation in the Indonesian legal system. The research uses a normative juridical method with a legislative approach and a conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials that are analyzed qualitatively through prescriptive analysis methods. The results of the study show that arbitration has advantages in the form of more flexible procedures, relatively fast dispute resolution, process secrecy, and freedom of the parties to choose arbitrators who have competence according to the character of business disputes. Nonetheless, the effectiveness of arbitration has not been fully determined by procedural efficiency as the implementation of awards still depends on the support of judicial institutions, particularly in the process of execution and annulment of arbitral awards. Therefore, the effectiveness of arbitration can only be realized if procedural efficiency goes hand in hand with the certainty of the implementation of the award through the consistent application of the principle of final and binding and the limitation of court intervention in accordance with the provisions of laws and regulations.